The risk of consuming MTGase-restructured steaks like intact steaks - Zheng, Denny; BCIT School of Health Sciences, Environmental Health; Sidhu, Bobby; Keilbart, Ken; McIntyre, Lorraine (BCIT Environmental Public Health Journal, 2014)
Introduction: The use of transglutaminase to restructure loose pieces of meat into a fully intact piece of steak has been a concern for the public because of the potential internalization of contaminated surfaces into the aseptic center. The aim of this study was to examine if restructured steaks are safe to consume when cooked to medium rare, a common option with whole cut steaks Methods: Strips of beef were inoculated with E.coli to induce surface contamination. Steaks were restructured with transglutaminase and the altered meat. These steaks were then cooked alongside fully intact whole-cut steak samples. Each sample was then churned in a stomacher, and the resulting solution was used to detect for potential E.coli bacteria. Samples were then enriched and finally placed into the Hygiena Micro-snap Rapid Coliform and E.coli detection test to look for the presence of E.coli. Results: The Hygiena system showed that all transglutaminase restructured steaks possessed detectable levels of E.coli even after cooking to 55 degrees Celsius. On the other hand, no whole-cut steaks had traces of E.coli even when cooked to this same temperature. Conclusion: The results demonstrated that there is a substantial risk with restructured steaks and they should not be consumed undercooked. As well, proper labelling and guidelines should be developed to enable consumers to be better equipped in making decisions to consume properly consumed altered steaks.